PENGARUH PENDIDIKAN DAN PENGANGGURAN TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) DI PULAU JAWA TAHUN 2010-2023 - Shoolihah, Muhayyijah Fil Qurbah; Musyaropah (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2024)
An important indicator for evaluating the success of a region's economic policies and determining the classification of a country as developed, developing or underdeveloped is the Human Development Index (HDI). The aim of this research is to find out how the Human Development Index (HDI) on the island of Java is influenced by unemployment (open unemployment rate) and educational characteristics (average years of schooling). The Central Statistics Agency (BPS) provides secondary sources in the form of data for 2010–2023 covering six provinces on the island of Java: DKI Jakarta, West Java, DIY, Central Java, East Java and Banten which are used in this research. Using E-Views 12 software, a multiple regression approach was used for analysis. The findings of this study show that the Human Development Index (HDI) is significantly influenced by a combination of these two factors. On the Human Development Index, the education variable has a fairly large positive influence, while the unemployment variable has a significant negative influence.